PERBEDAAN PERTUMBUHAN DAN PERKEMBANGAN PADA ANAK USIA PRASEKOLAH (3-5 TAHUN) YANG MEMILIKI IBU BEKERJA DAN IBU YANG TIDAK BEKERJA DI TK STA. MARIA ASSUMPTA KOTA KUPANG - Maria Asqueli (STIKes CHMK, 2018)
Background: Growing up is an aspect that explains the process of forming a person both physically and psychosocialy. Disorders occurring in preschool children if not detected and not handled properly will reduce the quality of human resources in the future. It is demanded the role of mother as a determinant of parenting to care for and protect children to achieve optimal growth and development. Objective: To identify differences in growth and development of pre-school children (3-5 years old) who have working mothers and non-working mother in Sta. Maria kind garden Assumpta Kota Kupang. Method: This research is a quantitative research design with comparative descriptive approach. Respondents were 52 respondents taken with Purposive Sampling technique. The instruments of data collection are: anthropometric measurement and observation sheet of denver II data analysis using Mann-Wihtney test. Result: The result of statistical test for growth was obtained p value = 0,027 (p <0,05) which showed that there was significant difference in growth between preschool children (3-5 years old) who have working mother and non-working mother while for the development obtained p value = 0.641 (p> 0.641) which shows that there is no significant difference between development of preschool children (3-5 years old) who have working mothers and non-working mother. Suggestion: Researcher give suggestion to working mother to pay more attention to children growth and give adequate stimulation for children development. Keywords: Growth and development of pre-school children, working mother, non-working mother.